2017
DOI: 10.5604/12321966.1228952
|View full text |Cite
|
Sign up to set email alerts
|

Number of <i>Streptococcus mutans</i> and <i>Lactobacillus</i> in saliva versus the status of cigarette smoking, considering duration of smoking and number of cigarettes smoked daily

Abstract: The number of SM and LB in saliva does not depend on the smoking status, the number of cigarettes smoked daily and duration of smoking.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 15 publications
0
8
1
Order By: Relevance
“…Six studies sampled both males and females, while five only included males. One study 20 assessed smoking using self-report and cotinine tests, the remaining studies used self-report only. Seven studies 15-21,23 analyzed DMFT and one 22 analyzed DMFS.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Six studies sampled both males and females, while five only included males. One study 20 assessed smoking using self-report and cotinine tests, the remaining studies used self-report only. Seven studies 15-21,23 analyzed DMFT and one 22 analyzed DMFS.…”
Section: Resultsmentioning
confidence: 99%
“…Two studies 11,19 accessed both. One study 20 reported the levels of Streptococcus mutans (SM) and Lactobacillus (LB).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, lower levels of F. nucleatum and Leptotrichia have been detected in patients who smoke and have OLP [108]. Nonetheless, the levels of S. mutans and Lactobacillus have been observed to be unchanged even with regular smoking [114]. Elevated levels of R. mucilaginosa, Veillonella, Streptococcus, and Leptotrichia have been connected to OSCC independently, without the presence of smoking [47, 108, 113, 115-118].…”
Section: Tobacco and Ethanolmentioning
confidence: 99%
“…However, external factors may also affect microbial diversity in the salivary microbiota. Among these external factors, tobacco smoking has been shown to affect the oral microbiota (5, 6). Later studies however did not rely on culture (5), or were restricted to a few Gram-positive bacterial species (6).…”
Section: Introductionmentioning
confidence: 99%